Implementation of a closed platelet-rich-plasma preparation method using the local blood bank infrastructure at the Principality of Asturias (Spain): Back to basic methodology and a demographics perspective after 1 year. (October 2019) - Ojea-Pérez, Ana María; Acebes-Huerta, Andrea; Arias-Fernández, Tamara; Gutiérrez, Laura; Muñoz-Turrillas, María Carmen
Abstract: Platelet-rich plasma (PRP) is used with increasing demand as autologous adjuvant therapy in many areas of regenerative medicine, thanks to the platelet rich content of growth factors and bio-active molecules. However, to date there is a lack of consensus on PRP preparation methods, on processing and application forms, on clinical application guidelines and on knowledge-based composition at the cellular and molecular level, making difficult the assessment of clinical results from different groups in different clinical areas. Here we describe the implementation of PRP production on a closed-system using the infrastructure of a certified blood bank, detailing methodology, and validation and production results 1 year after its implementation. Our methodology provides a reproducible, safe, practical and yet affordable PRP bio-product that will allow further studies to better define PRP applications in regenerative medicine and personalized therapeutic regimes.